The Phenomenon of Cultural Codes in the Light of Linguodidactics - Макарова, Ольга (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The article deals with peculiarities of teaching codes of the Russian linguistic culture to foreign students, special attention is paid to selection of material, choice for texts used in practical classes, characterized by individual specificity of perception and presentation. Many objects of the world around us, in addition to performing their direct functions, acquire a sign function and become capable of carrying some additional values, called codes of culture. Knowledge of standards, stereotypes, mythologies, rituals, customs, existing in the language is one of the main components of linguistic and cultural competence that characterizes the subject of speech communication. The most striking units of the cultural code as clusters of cultural and national standards are manifested in phraseological units. Identification and description of units of cultural code is relevant for modern linguo-didactics, since the realities used in phraseological units, having passed a certain “filtration” of time and culture, were involved in the figurative description of the world picture of representatives of the Russian linguistic and cultural community.